2012
DOI: 10.1111/j.1741-6787.2012.00251.x
|View full text |Cite
|
Sign up to set email alerts
|

Lesbian, Gay, Bisexual, and Transgender Parents Seeking Health Care for Their Children: A Systematic Review of the Literature

Abstract: Further research is required to explore LGBT-parented families' experiences of healthcare services, and this should include children's experiences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 37 publications
2
52
0
Order By: Relevance
“…The topic of lesbians' encounters with reproductive healthcare has largely been researched internationally (Cherguit, Burns, Pettle, & Tasker, 2013;Dahl, Fylkesnes, Sørlie & Malterud, 2013;Dahl Spidsberg, 2007;Hayman et al, 2013;McManus, Hunter & Renn, 2006;Peel, 2010;Shields et al, 2012;Wilton & Kaufmann, 2001), and somewhat researched in Sweden (Larsson & Dykes, 2009;Röndahl et al, 2009). Previous studies in the field generally describe patients' experiences as such, often pointing both at positive aspects of encounters, such as meeting with competent and well-informed staff, and at discrimination and prejudices.…”
Section: Chapter VI Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The topic of lesbians' encounters with reproductive healthcare has largely been researched internationally (Cherguit, Burns, Pettle, & Tasker, 2013;Dahl, Fylkesnes, Sørlie & Malterud, 2013;Dahl Spidsberg, 2007;Hayman et al, 2013;McManus, Hunter & Renn, 2006;Peel, 2010;Shields et al, 2012;Wilton & Kaufmann, 2001), and somewhat researched in Sweden (Larsson & Dykes, 2009;Röndahl et al, 2009). Previous studies in the field generally describe patients' experiences as such, often pointing both at positive aspects of encounters, such as meeting with competent and well-informed staff, and at discrimination and prejudices.…”
Section: Chapter VI Discussionmentioning
confidence: 99%
“…Having a child in a planned lesbian family often directly involves healthcare services or welfare institutions, such as fertility clinics, maternal health care or adoption agencies. Accordingly, a great number of studies regard lesbians' encounters with such institutions (Brown et al, 2009;Cherguit, Burns, Pettle, & Tasker, 2013;Dahl, Fylkesnes, Sørlie & Malterud, 2013;Dahl Spidsberg, 2007;Goldberg, Weber, Moyer & Shapiro, 2014;Hayman et al, 2013;;Kinkler & Goldberg, 2011;McManus, Hunter & Renn, 2006;Mallon, 2011;Peel, 2010;Ross et al 2008Ross et al , 2009Ryan & Withlock, 2007;Shields et al, 2012;Wilton & Kaufmann, 2001). These studies generally highlight discrimination and prejudices, labelled as heteronormativity, heterosexism or homophobia, depending on the researcher's epistemological and theoretical background.…”
Section: Studies On Lesbian Family Life and Practicesmentioning
confidence: 99%
“…Research has shown that many lesbian, gay and bisexual (LGB) parents are unwilling to discuss their gender identity for fear of discrimination (Neville & Henrickson, ; Shields et al., ). This fear may cause them to avoid seeking healthcare for themselves and their children (Chapman, Wardrop, Freeman et al., ; Chapman, Wardrop, Zappia, Watkins, & Shields, ; Röndahl, ).…”
Section: Introductionmentioning
confidence: 99%
“…,b,c,d,e, Shields et al . ,b). The consequences of nondisclosure can include leaving parents mistrusting, ill informed and can result in missed opportunities for health education (Perrin & Kulkin , Chapman et al .…”
Section: Introductionmentioning
confidence: 99%